2018
DOI: 10.3389/fnbeh.2018.00145
|View full text |Cite
|
Sign up to set email alerts
|

Post-weaning Environmental Enrichment in Male CD-1 Mice: Impact on Social Behaviors, Corticosterone Levels and Prefrontal Cytokine Expression in Adulthood

Abstract: Environmental enrichment is typically associated with enhanced well-being, improved cognitive function and stress resilience. However, in some instances grouping adult male mice in enriched conditions promoted a stressful environment, which resulted in elevated endocrine, monoamine and inflammatory outcomes in response to subsequent stressor exposure. The current investigation examined whether raising male mice in an enriched environment (EE) would modulate social and anxiety-like behaviors in early adulthood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Although the raw scores were not significantly different among the three groups, the HI EE group and NOR intact group had significantly fewer total entries than the HI control group (** p < 0.01, * p < 0.05). This result is similar to the maze results of previous studies, and indicates that long-term exposure to EE may decrease levels of anxiety, as indicated by the significantly low number of total entries [49,50]. Overall, HI EE mice and NOR intact mice had a significantly higher alterative behavior percent compared to that of HI control mice (* p < 0.05, ** p < 0.01, The HI EE group and the NOR group significantly outperformed the HI control group throughout the study period.…”
Section: Ee Improves Short-term Spatial Memory In Hie Micesupporting
confidence: 90%
“…Although the raw scores were not significantly different among the three groups, the HI EE group and NOR intact group had significantly fewer total entries than the HI control group (** p < 0.01, * p < 0.05). This result is similar to the maze results of previous studies, and indicates that long-term exposure to EE may decrease levels of anxiety, as indicated by the significantly low number of total entries [49,50]. Overall, HI EE mice and NOR intact mice had a significantly higher alterative behavior percent compared to that of HI control mice (* p < 0.05, ** p < 0.01, The HI EE group and the NOR group significantly outperformed the HI control group throughout the study period.…”
Section: Ee Improves Short-term Spatial Memory In Hie Micesupporting
confidence: 90%
“…Animals were housed at the Centro de Biología Molecular “Severo Ochoa” (CBMSO) in a specific pathogen-free colony facility in accordance with European Community Guidelines (directive 86/609/EEC) and handled following European and local animal care protocols. Given that the hierarchy/dominance relationships established between male mice have a negative impact on AHN (Kozorovitskiy and Gould, 2004; McQuaid et al, 2018), only female mice were used in this work in all the housing conditions tested. Animals were left undisturbed for 2 weeks before starting any experimental manipulation.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, one of the compartments held a non-familiar female mouse. The percentage of time the animals spent interacting with this mouse (either relative to the total exploratory or the total testing time) was calculated as a measurement of social interaction (McQuaid et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The need to evaluate how agonistic interactions and dominant-subordinate relationships in male rodents may change as a consequence of being housed in EE has been highlighted in different reports (Cao et al, 2017;Giles et al, 2018;Hutchinson et al, 2012;Lima & Spinelli de Oliveira, 2014;Van Loo et al, 2003). Some studies have suggested that the presence of novel objects in the cage and the complexity of the environment enhance aggressive behaviors due to the competition for resources or physical proximity between animals (Abou-Ismail, 2011;Giles et al, 2018;McQuaid et al, 2013;McQuaid et al, 2018), the elimination of territorial odor-marking or failure to control the environment (Kaliste et al, 2006;Van Loo et al, 2001). Previous studies have indicated that male NMRI mice maintained in EE for 4 weeks display enhanced sociability and increased agonistic behaviors (Mesa-Gresa et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%